The effect of guideline-based antimicrobial therapy on the outcome of fracture-related infections (EAT FRI Study). Issue 3 (March 2023) - Corrigan, Ruth; Sliepen, Jonathan; Rentenaar, Rob J; IJpma, Frank; Hietbrink, Falco; Atkins, Bridget L; Dudareva, Maria; Govaert, Geertje AM; McNally, Martin A; Wouthuyzen-Bakker, Marjan
Highlights: Fracture-related infection (FRI) is a devastating complication of musculoskeletal trauma and often requires multiple surgeries and long-term antibiotic treatment. Antibiotic FRI recommendations have been published and provide valuable and practical guidance in FRI treatment. Strict compliance to the FRI recommendations is not mandatory if antibiotic treatment is advised by an experienced team and if appropriate surgery has been performed. Abstract: Aim: This study investigated the compliance with a guideline-based antibiotic regimen on the outcome of patients surgically treated for a fracture-related infection (FRI). Method: In this international multicenter observational study, patients were included when diagnosed with an FRI between 2015 and 2019. FRI was defined according to the FRI consensus definition. All patients were followed for at least one year. The chosen antibiotic regimens were compared to the published guidelines from the FRI Consensus Group and correlated to outcome. Treatment success was defined as the eradication of infection with limb preservation. Results: A total of 433 patients (mean age 49.7 ± 16.1 years) with FRIs of mostly the tibia (50.6%) and femur (21.7%) were included. Full compliance of the antibiotic regime to the published guidelines was observed in 107 (24.7%) cases. Non-compliance was mostly due to deviations from the recommended dosing, followed by the administration of an alternative antibiotic than the one recommended or an incorrect use or non-use of rifampin. Non-compliance was not associated with a worse outcome: treatment failure was 12.1% in compliant versus 13.2% in non-compliant cases ( p = 0.87). Conclusions: We report good outcomes in the treatment of FRI and demonstrated that minor deviations from the FRI guideline are not associated with poorer outcomes.